2002
DOI: 10.1186/bcr537
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of lysozyme in male breast cancer

Abstract: FBC = female breast cancer; HSCORE = histological score; MBC = male breast cancer; RFS = relapse-free survival.Available online http://breast-cancer-research.com/content/4/6/R16 AbstractBackground: Lysozyme, one of the major protein components of human milk that is also synthesized by a significant percentage of breast carcinomas, is associated with lesions that have a favorable outcome in female breast cancer. Here we evaluate the expression and prognostic value of lysozyme in male breast cancer (MBC). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Having a molecular weight of 14.4 kDa with a primary sequence containing 129 amino acids and an isoelectric point of 11.0, lysozyme is a ubiquitous enzyme widely available in diverse organisms such as bacteria, bacteriophages, fungi, plants and mammals [ 4 , 5 ]. Lysozyme also plays an important role as a biomarker for diagnosing diseases such as breast cancer [ 6 ], Alzheimer’s disease [ 7 ], rheumatoid arthritis [ 8 ], malaria [ 9 ], AIDS [ 10 ], tuberculosis and leprosy [ 11 ], sarcoidosis [ 12 ], and Crohn’s disease [ 13 ]. Typically, the concentration of lysozyme in a healthy person’s saliva is 13.8 µg/mL [ 14 ], whereas the concentration is 0.463–2.958 µg/mL in a healthy person’s serum [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having a molecular weight of 14.4 kDa with a primary sequence containing 129 amino acids and an isoelectric point of 11.0, lysozyme is a ubiquitous enzyme widely available in diverse organisms such as bacteria, bacteriophages, fungi, plants and mammals [ 4 , 5 ]. Lysozyme also plays an important role as a biomarker for diagnosing diseases such as breast cancer [ 6 ], Alzheimer’s disease [ 7 ], rheumatoid arthritis [ 8 ], malaria [ 9 ], AIDS [ 10 ], tuberculosis and leprosy [ 11 ], sarcoidosis [ 12 ], and Crohn’s disease [ 13 ]. Typically, the concentration of lysozyme in a healthy person’s saliva is 13.8 µg/mL [ 14 ], whereas the concentration is 0.463–2.958 µg/mL in a healthy person’s serum [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme is one of the major protein components of human milk, but it is also synthesized by various types of cancer cells [ 20 , 21 ]. The expression of lysozyme was positively correlated with a favorable outcome in breast cancer [ 20 ] and was upregulated to a greater extent in mucinous cell carcinomas than in well-differentiated and poorly differentiated gastric adenocarcinomas [ 21 ]. Lysozyme directly activates immune cells and increases tumor cell immunogenicity [ 22 ], which have been confirmed in a number of experimental cases [ 22 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mammaglobin-A has previously been used for the non-invasive, in vivo detection of cancerous cells in mouse breast cancer with metastatic axillary lymph nodes and has shown a high resolution and specificity, indicating a potential for future translation into the provision of clinical guidance (13). Serra et al (14) reported that lysozyme-positive male breast cancer has an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%